Rancang Bangun Keakurasian Penjadwalan Waktu Shalat Menggunakan Metode Julian Day dan Metode Scanning - Suroso Suroso; Viona Rucita; Ciksadan Ciksadan (LPPM STIKI MALANG, 2022)
5 times prayer is an obligation that must be done by every muslim. Therefore, information regarding the prayer time is important for every muslim. In this study, the calculation method of the Julian Day algorithm and the scanning method were applied to accurately schedule prayer times on the dot matrix LED panel, where this tool will later be implemented in the Hidayatullah Mosque and function as an information board for prayer times with output displayed in the form of running text and features additional playback of murals automatically at the time of the call to prayer. The prayer schedule calculation method uses Julian Day as a reference for publishing prayer schedules based on the declination of the sun and can be calculated accurately with the reference coordinates and calendar values ​​which will be compared with the prayer times set by the ministry of religion. The results obtained from this test will display prayer times, sunnah fasting schedules, Hijri calendar, Christian calendar, day, month, year and some other information that is displayed through running text so that it can help Muslim communities fulfill their obligations. The accuracy of determining the prayer hours obtained from the calculation of the tool has an accuracy level with a maximum error tolerance of 1 minute, which can be caused by differences in determining the position of the coordinates between the provisions of the schedule released by the ministry of religion and the testing location.